A Combined Optimization Method for the Transition Control Schedules of Aero-Engines - Wang Hao; Xiaobo Zhang; Baokuo Li; Zhanxue Wang; Dawei Li (Aerospace, 2025)
A well designed transition control schedule can enable the engine to quickly and smoothly transition from one operating state to another, thereby enhancing the maneuverability of the aircraft. Although traditional pointwise optimization methods are fast in solving the transition control schedules, their optimized control schedules suffer from fluctuation problems. While global optimization methods can suppress fluctuation problems, their slow solving speed makes them unsuitable for engineering applications. In this paper, a combined optimization method for the transition control schedules of aero-engines is proposed. This method divided the optimization of the control schedules into two layers. In the outer-layer optimization, the global optimization technique was utilized to suppress the fluctuation of geometrically adjustable parameters. In the inner-layer optimization, the pointwise optimization technique was adopted to quickly obtain the control schedule of fuel flow rate. Moreover, a construction method of non-uniform control points in the global optimization layer was proposed, which significantly reduced the number of control points that needed to be optimized; thus, improving the efficiency of global optimization. The optimization problem of the acceleration and deceleration control schedules of a mixed-flow turbofan engine was used to verify the effectiveness of the combined optimization method. The results show that, compared with the pointwise optimization method, the transition time optimized by the combined optimization method shows no obvious difference. The control schedules optimized by the combined optimization method are not only smooth but can also prevent some components from approaching their working boundaries.